Pathological Response Assessment following Long Course Neoadjuvant Chemoradiation in Locally Advanced Rectal Cancer: A Single Institutional Cohort Study - Maria Baby; Jomon Raphael; B Rajkrishna; Mathew Varghese; Febin Antony (Journal of Clinical and Diagnostic Research)
Introduction: Neoadjuvant chemoradiation and Total Mesorectal Excision (TME) have shown pathological complete response (pCR) rates of 15-27%. The pCR is a significant predictor of survival. The Mandard Tumour Regression Grading (TRG) system is used to report pathological response. Aim: To evaluate the pathological response in patients with locally advanced rectal cancer undergoing neoadjuvant chemoradiation and to investigate Disease-Free Survival (DFS). Materials and Methods: This single-centre cohort ambispective study was conducted from January 2019 to July 2023 at the Amala Institute of Medical Sciences, Thrissur, Kerala, India. It included patients aged 18-75 years with T3, T4, any NM0, and any T, N1, N2M0 rectal cancer, with an Eastern Cooperative Oncology Group (ECOG) performance status of 1-2. Patients who did not undergo surgery or chemotherapy at our centre, those who refused surgery, and those planned for Total Neoadjuvant Therapy (TNT) or short-course radiation therapy were excluded. Thirty-nine patients meeting the criteria were included in the study. All patients underwent neoadjuvant chemoradiation using Intensity Modulated Radiation Therapy (IMRT) to a dose of 50.4 Gy in 28 fractions over five and a half weeks, combined with concurrent chemotherapy using Capecitabine 825 mg/m² twice daily. All operable patients subsequently underwent TME, followed by adjuvant chemotherapy. Pathological response was assessed using Mandard TRG. Results: Thirty-nine patients were enrolled. The most common tumour location was found to be between 6-10 cm from the anal verge (22, 56.41%). The most frequent radiological T stage was T3, constituting 26 patients (66.67%), and 16 patients (41.03%) presented with N2 disease. TRG 1 was observed in seven patients (17.95%), TRG 2 in six patients (15.38%), TRG 3 in 21 patients (53.85%), TRG 4 in four patients (10.26%), and TRG 5 in one patient (2.56%). The median follow-up time was 24 months (range: 3-60 months). The two-year DFS was 86%. Conclusion: Neoadjuvant chemoradiation in locally advanced rectal cancer demonstrated meaningful pathological tumour regression and encouraging DFS outcomes.